Glass paste for platinum film thermosensitive resistor and preparation method of glass paste
By using RO-SiO2-Al2O3-based encapsulated glass material to adjust the oxide content and melting process, the problems of low softening temperature and reduced insulation resistivity of existing glass materials are solved, and the glass material works for a long time at 500℃ Stability and packaging reliability.
Patent Information
- Application Number
- CN202411578868.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-14
AI Technical Summary
The softening temperature of existing glass materials is low, which cannot meet the high-temperature working needs of platinum thin-film thermistors. At the same time, the insulation resistivity of the glass is easily reduced under high temperature conditions, affecting the accuracy and reliability of the resistor.
The RO-SiO2-Al2O3-based encapsulated glass material is adopted to adjust the oxide content and melting process to improve the softening temperature and high-temperature insulation resistivity of the glass, and reduce the expansion coefficient, and optimize the bonding performance between the glass and the substrate.
The stability of glass material working at 500℃ for a long time is achieved, and the packaging temperature is reduced, the bonding strength between glass material and substrate and the reliability of packaging is improved, and the high-temperature working needs of platinum resistance film temperature sensor is met.
Smart Images

Figure CN119430643A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass materials, and in particular to a glass paste for a platinum thin film thermistor and a preparation method thereof. Background Art
[0002] As a commonly used core component for temperature measurement, thin film thermistors have been widely used in the market. In addition to being used in traditional industries such as petroleum and chemical industry, they are also commonly used in the measurement and control of medical equipment, analytical instruments, electronic heating equipment, biopharmaceutical equipment, and the automotive industry. Compared with general metal film thermistors, platinum thin film thermistors have the advantages of good linearity, good stability, high accuracy, and a large temperature measurement range. They are the preferred solution for temperature measurement of special components such as spacecraft antennas, solar cell arrays, and attitude and orbit control engines, and are widely used in aviation, aerospace and other fields.
[0003] Although platinum thin film thermistors are widely used, they are limited by raw materials and have a large gap with foreign countries in terms of quality, cost performance and commercialization, and the domestic market share is low. Among them, the packaging glass material mainly affects the product's temperature coefficient, temperature measurement range, test accuracy, environmental interference resistance and other key technical indicators; but there is currently little research on glass materials, and high-temperature measurement capabilities are restricted by glass materials.
[0004] The domestic packaging glass system is mainly based on borosilicate glass (Na2O-K2O-Al2O3-B2O3-SiO2). The softening temperature of this system is low and cannot meet the working temperature requirements of platinum thin film thermistors. At the same time, since it contains a large amount of alkali metal ions, it is easier to migrate rapidly in the network structure under high temperature conditions, resulting in a sharp decrease in the high-temperature insulation resistivity of the glass. In addition, the alkali metal ions will diffuse with the platinum atoms at the glass-platinum packaging interface, reducing the purity of the platinum film and affecting the temperature coefficient of the platinum resistance and the resistance accuracy. For example, the invention application with application number 202310627219.3 discloses a method for preparing a glass ceramic sealing material for platinum resistance thin film temperature sensor, and the specific steps are: S1, mixing glass raw materials and subjecting them to a first ball milling, drying and sieving to obtain glass raw material powder, wherein the glass raw materials include 30-40 parts of B2O3, 15-20 parts of SiO2, 10-15 parts of Al2O3, and 20-30 parts of CaO; S2, placing the glass raw material powder in a ceramic crucible and heating it to 1400-1500°C, and obtaining liquid glass after high temperature melting; S3, mixing the liquid glass Pour the glass into water for water quenching to obtain glass slag; S4, place the glass slag in a dust-free sealed environment, and after the glass slag cools to room temperature, place it in a planetary ball mill for a second ball milling, grind for 24 hours to obtain glass powder; S5, use a thermal expansion instrument to detect the characteristic temperature of the glass powder; S6, after drying the glass powder, mix the glass powder with alumina powder in a certain proportion to form a mixed powder, place it in a planetary ball mill for a third ball milling to mix evenly, and mix for 12 hours to obtain glass ceramic sealing powder; 80-90 parts of glass powder and 10-20 parts of alumina powder;
[0005] S7. Mix glass ceramic sealing powder and organic carrier in a certain proportion to form glass ceramic sealing slurry, and use screen printing technology to coat the prepared glass ceramic sealing slurry on the platinum circuit ceramic chip, printing 2 to 5 layers; S8. Put the platinum circuit ceramic chip coated with the glass ceramic sealing slurry into a temperature-controlled furnace, heat it to 850°C at a heating rate of 3°C / min, keep it warm for 60 minutes, and obtain the glass ceramic sealing material after cooling.
[0006] A German company has invested a lot of R&D funds to study high-temperature packaging glass and developed a series of glass packaging materials that can work stably at high temperatures, providing reliability guarantees for resistors with high precision, good linearity and good stability. In order to meet the current needs of independent localization research on platinum thin film resistors, we urgently need to develop a packaging glass material that can work stably at high temperatures.
[0007] The present invention selects RO-SiO2-Al2O3 based encapsulation glass material for research. The glass of this system has the advantages of high softening temperature, good chemical stability, high high-temperature insulation resistivity, adjustable expansion coefficient, etc. By studying the influence of different oxide contents and melting processes on the performance of glass materials, the components are further designed and optimized to obtain an encapsulation glass material with excellent performance. Summary of the invention
[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a glass paste for platinum thin film thermistors and a preparation method thereof. By controlling the ball milling process, a glass powder with an average particle size of 3 to 10 μm is obtained. The glass powder with a suitable particle size has good dispersibility and fluidity during the sintering process. The density of the sintered product is improved, the porosity is reduced, the surface is relatively flat, and the wettability of the glass and the substrate is relatively strong. At the same time, the sintering temperature is reduced, the sintering holes are improved, the packaging reliability is improved, and the demand for lead-free glass materials for resistors is met. At present, the packaging glass material that can meet the requirements of stable operation at 500°C generally has a packaging temperature of >800°C; while the present invention provides a glass material that can work at 500°C for a long time and has a packaging temperature of <700°C.
[0009] The technical solution adopted by the present invention to solve the technical problem is: a glass paste for platinum thin film thermistor, the glass paste mainly comprises the following components by weight percentage: 50% to 75% of lead-free glass material, 0% to 5% of inorganic additives, and the balance is organic additives; the lead-free glass material is a SiO2-B2O3-Bi2O3-CaO-Al2O3 system, and mainly comprises the following components by weight percentage: 28.05% to 28.45% of silicon oxide, 30.31% to 30.75% of boron oxide, 8.67% to 8.80% of aluminum oxide, 7.07% to 11.52% of bismuth oxide, 0% to 3.33% of lithium oxide, 9.08% to 12.85% of zinc oxide, 6.68% to 6.77% of calcium oxide, 1.85% to 1.88% of titanium dioxide, and 0.1% to 0.3% of cobalt oxide.
[0010] Furthermore, the inorganic additive is nano-alumina.
[0011] Furthermore, the organic additive mainly comprises the following components in terms of weight percentage: 60% to 80% of solvent pineol, 2% to 4% of plasticizer butyl benzyl phthalate, 8% to 14% of emulsifier, and 2% to 10% of binder.
[0012] Furthermore, the binder includes at least one of polyvinyl butyral (PVB) and ethyl cellulose.
[0013] A method for preparing glass paste for platinum thin film thermistor, the method specifically comprising the following steps:
[0014] S1. Weigh each component of the lead-free glass material by weight percentage and mix them evenly using a mixer;
[0015] S2, keeping the temperature at 1100-1450°C for 40-70 minutes, quenching the glass liquid with water to obtain glass slag, and drying it in an oven at 100°C for more than 4 hours;
[0016] S3, placing the glass slag in a planetary ball mill for crushing to obtain glass powder; the particle size D50 of the glass powder is less than 10 μm;
[0017] S4. Cast a regular rectangular glass rod during the water quenching process, grind and polish it, and then test the intrinsic thermal properties of the glass material, including the thermal expansion coefficient and softening temperature;
[0018] S5. Under heating conditions, adding various components of the organic additive into a container, stirring the various components evenly, and obtaining a transparent pre-dissolved organic solution;
[0019] S6. Add the glass powder obtained in S3 and the pre-dissolved organic solution obtained in S5 into a vacuum mixer and stir them evenly to obtain glass slurry.
[0020] Furthermore, in S5, the organic additives include a binder, a solvent pineneol, a plasticizer butyl benzyl phthalate and an emulsifier; first, under heating and stirring conditions, the solvent pineneol is added to the container, and then the binder is slowly added to the solvent, and when the binder is completely dissolved in the solvent, the temperature is reduced and stirred; finally, the plasticizer butyl benzyl phthalate and the emulsifier are added, and after stirring evenly, a transparent pre-dissolved organic solution is obtained, which is left to stand for use.
[0021] Furthermore, in S3, the ball milling process uses agate balls with diameters of 6 mm, 8 mm, and 12 mm as medium balls, and the mass ratio of medium balls of each diameter is 1.5-2:2-3:1.5-2; the mass ratio of glass slag to medium balls is 1-2.5:0.8-1, and the ball milling time is 1.5-6 h; the above ball milling process parameters are used for two ball millings to obtain glass powder of suitable particle size.
[0022] Furthermore, after the glass slurry is coated on the surface of the ceramic substrate, it is sintered, and the performance of the sintered glass-ceramic element is tested. The sintering process is specifically to keep the temperature at 120-150°C for 5 minutes, keep the temperature at 330-350°C for 5 minutes, and keep the temperature at 500°C to 610°C for 10 to 30 minutes to obtain a dense encapsulation layer. The sintered glass-ceramic element is observed under an optical microscope to observe its glass sintering state, and the glass must be free of bubbles and dense. The packaged element is then subjected to a tensile test. After 20 sample tests, the average tensile value is greater than 13N, which meets the packaging requirements.
[0023] The beneficial effects of the present invention are as follows: compared with the prior art, the glass paste for platinum thin film thermistor provided by the present invention and its preparation method use calcium oxide and silicon oxide as the matrix, which ensures the high temperature working stability of the glass material; zinc oxide can appropriately reduce the glass transition temperature, reduce the thermal expansion coefficient of the material, improve the sintering compatibility with the substrate, and at the same time reduce the surface tension between the ceramic substrate and the glass phase to improve the wettability; calcium oxide can react with aluminum oxide on the surface of the ceramic substrate to reduce the stress generated by the mismatch of the thermal expansion coefficient during sintering; bismuth oxide is effective in fluxing and has stable chemical properties. The introduction of bismuth oxide reduces the melting temperature of the ternary Si-Ca-Al glass material while ensuring the chemical stability of the material and ensuring the wide high temperature operation of the component. The combined effect of the three oxides can ensure the stability of the glass transition temperature while appropriately reducing the softening temperature, thereby reducing the sintering temperature of the paste, reducing the mutual diffusion of elements between the interfaces, having a small resistance change, and enhancing the reliability of the component; at the same time, the adhesion between the glass material and the interfaces of the substrate is enhanced; thereby obtaining a defect-free and well-adhesive encapsulated glass material. By adding lithium oxide, the expansion coefficient and thermal ease of glass are reduced, and the heat resistance of glass is increased; zinc oxide and bismuth oxide reduce the softening point of glass materials and improve the fluidity during melting; boron trioxide reduces the melting temperature of glass and inhibits the increase of the thermal expansion coefficient of glass. The present invention solves the problems existing in the prior art, such as the mismatch between thermal expansion and substrate, narrow sintering temperature range, and low packaging strength. After packaging, the glass has no bubbles inside, high density, and high bonding strength with the substrate, and the tensile value is greater than 13N, which can meet the long-term safety requirements of platinum resistance thin film temperature sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a melting temperature curve of the glass material used for the platinum thin film thermistor in Example 1.
[0025] Figure 2 Graph showing the thermal expansion coefficient of the glass material used in the platinum thin film thermistor in Examples 1 to 5.
[0026] Figure 3This is an appearance morphology picture of the platinum thin film thermistor under an optical microscope after sintering the glass paste and the ceramic substrate in Example 1. DETAILED DESCRIPTION
[0027] The present invention is further described below by specific examples, but these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0028] Example
[0029] A glass paste for platinum thin film thermistor, the glass paste mainly comprises the following components by weight percentage: 50% to 75% of lead-free glass material, 0% to 5% of inorganic additives, and the balance is organic additives; the lead-free glass material is a SiO2-B2O3-Bi2O3-CaO-Al2O3 system, and mainly comprises the following components by weight percentage: 28.05% to 28.45% of silicon oxide, 30.31% to 30.75% of boron oxide, 8.67% to 8.80% of aluminum oxide, 7.07% to 11.52% of bismuth oxide, 0% to 3.33% of lithium oxide, 9.08% to 12.85% of zinc oxide, 6.68% to 6.77% of calcium oxide, 1.85% to 1.88% of titanium dioxide, and 0.1% to 0.3% of cobalt oxide.
[0030] The inorganic additive is nano-alumina. The organic additive mainly includes the following components by weight percentage: 60% to 80% of solvent pine alcohol, 2% to 4% of plasticizer butyl benzyl phthalate, 8% to 14% of emulsifier, and 2% to 10% of binder. The binder includes at least one of polyvinyl butyral (PVB) and ethyl cellulose.
[0031] A method for preparing glass paste for platinum thin film thermistor, comprising the following steps:
[0032] S1. Weigh each component of the glass material according to weight percentage and mix them evenly using a mixer.
[0033] S2. Keep the temperature at 1100-1450°C for 40-70 minutes, quench the molten glass with water to obtain glass slag, and dry it in an oven at 100°C for more than 4 hours.
[0034] S3. Place the glass slag in a planetary ball mill for crushing to obtain glass powder; the particle size D50 of the glass powder is less than 10 μm.
[0035] S4. During the water quenching process, a regular rectangular glass rod is cast, and after grinding and polishing, the intrinsic thermal properties of the glass material, including the thermal expansion coefficient and softening temperature, are tested.
[0036] S5. Turn on the heat-collecting magnetic stirring heater and raise the temperature to 90° C. Add 50-60 g of pinene alcohol into a 250 ml beaker and place the beaker in the magnetic stirring heater.
[0037] S6. Weigh 1.4 g to 5 g of polyvinyl butyral (PVB), and slowly add the PVB into pinene alcohol. During this process, heat for about 30 minutes until the PVB is completely dissolved; cool down to 60°C, keep stirring for 30 minutes, and then cool down to 50°C.
[0038] S7. Add 2.8 g of plasticizer butyl benzyl phthalate and 9.8 g of emulsifier, stir for 30 min to obtain a transparent pre-dissolved organic solution, and let it stand.
[0039] S8. Add the glass powder obtained in S3 and the pre-dissolved organic solution obtained in S7 into a stirring kettle of a vacuum mixer, evacuate the kettle, and stir at 300 r / min for 30 minutes to obtain a uniform glass slurry.
[0040] S9. Apply the obtained glass slurry on 96% to 99% of the surface of the alumina ceramic by means of a spin coater.
[0041] S10, sintering the coated glass slurry-ceramic in a muffle furnace, keeping the temperature at 120-150° C. for 5 min, keeping the temperature at 330-350° C. for 5 min, and keeping the temperature at 500-610° C. for 10-30 min to obtain a dense encapsulation layer.
[0042] S11. Perform a tensile test on the encapsulated components. After 10 sample tests, the average tensile value is greater than 13N, meeting the packaging requirements.
[0043] Specific embodiments <![CDATA[SiO2]]> <![CDATA[B2O3]]> <![CDATA[Al2O3]]> <![CDATA[Bi2O3]]> <![CDATA[Li2O]]> ZnO CaO <![CDATA[Co2O3]]> <![CDATA[TiO2]]> sum Example 1 28.45 30.75 8.80 7.07 3.33 12.85 6.77 0.10 1.88 100.00 Example 2 28.25 30.53 8.73 9.19 1.65 12.76 6.72 0.30 1.86 100.00 Example 3 28.05 30.31 8.67 11.48 0.00 12.67 6.68 0.30 1.85 100.00 Example 4 28.30 30.58 8.75 9.31 3.31 10.95 6.73 0.20 1.87 100.00 Example 5 28.14 30.41 8.70 11.52 3.30 9.08 6.70 0.30 1.86 100.00
[0044] Compared with the prior art (CN 116354604 A), the melting temperature of the glass material is lowered by oxide doping, the thermal expansion coefficient of the material is smaller and the difference with the substrate is less than 3%, the glass transition temperature is stable, the softening temperature is lowered, the sintering temperature is lowered, and the high-temperature working temperature range is widened.
[0045] The above implementation modes are only used to illustrate the present invention, but not to limit the present invention. Ordinary technicians in the relevant technical field can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, all equivalent technical solutions also belong to the scope of the present invention. The patent protection scope of the present invention should be defined by the claims.
Claims
1. A glass paste for platinum thin film thermistor, characterized in that: The glass paste mainly comprises the following components by weight: 50% to 75% lead-free glass material, 0% to 5% inorganic additives, and the balance is organic additives; the lead-free glass material is a SiO2-B2O3-Bi2O3-CaO-Al2O3 system, and mainly comprises the following components by weight: 28.05% to 28.45% silicon oxide, 30.31% to 30.75% boron oxide, 8.67% to 8.80% aluminum oxide, 7.07% to 11.52% bismuth oxide, 0% to 3.33% lithium oxide, 9.08% to 12.85% zinc oxide, 6.68% to 6.77% calcium oxide, 1.85% to 1.88% titanium dioxide, and 0.1% to 0.3% cobalt oxide.
2. The glass paste for platinum thin film thermistor according to claim 1, characterized in that: The inorganic additive is nano-alumina.
3. The glass paste for platinum thin film thermistor according to claim 1, characterized in that: Calculated by weight percentage, the organic additive mainly includes the following components: 60% to 80% of solvent pine alcohol, 2% to 4% of plasticizer butyl benzyl phthalate, 8% to 14% of emulsifier, and 2% to 10% of binder.
4. The glass paste for platinum thin film thermistor according to claim 1, characterized in that: The binder includes at least one of polyvinyl butyral (PVB) and ethyl cellulose.
5. A method for preparing a glass paste for a platinum thin film thermistor as claimed in claim 1, characterized in that: The method specifically comprises the following steps: S1. Weigh each component of the lead-free glass material by weight percentage and mix them evenly using a mixer; S2, keeping the temperature at 1100-1450°C for 40-70 minutes, quenching the glass liquid with water to obtain glass slag, and drying it in an oven at 100°C for more than 4 hours; S3, placing the glass slag in a planetary ball mill for crushing to obtain glass powder; the particle size D50 of the glass powder is less than 10 μm; S4. Cast a regular rectangular glass rod during the water quenching process, grind and polish it, and then test the intrinsic thermal properties of the glass material, including the thermal expansion coefficient and softening temperature; S5. Under heating conditions, adding various components of the organic additive into a container, stirring the various components evenly, and obtaining a transparent pre-dissolved organic solution; S6. Add the glass powder obtained in S3 and the pre-dissolved organic solution obtained in S5 into a vacuum mixer and stir them evenly to obtain glass slurry.
6. The method for preparing a glass paste for a platinum thin film thermistor according to claim 5, characterized in that: In S5, the organic additives include a binder, a solvent pineneol, a plasticizer butyl benzyl phthalate and an emulsifier; first, under heating and stirring conditions, the solvent pineneol is added to a container, and then the binder is slowly added to the solvent. When the binder is completely dissolved in the solvent, the temperature is reduced and stirred; finally, the plasticizer butyl benzyl phthalate and the emulsifier are added, and after stirring evenly, a transparent pre-dissolved organic solution is obtained, which is left to stand for use.
7. The method for preparing a glass paste for a platinum thin film thermistor according to claim 5, characterized in that: In S3, the ball milling process uses agate balls with diameters of 6 mm, 8 mm, and 12 mm as medium balls, and the mass ratio of medium balls of each diameter is 1.5-2:2-3:1.5-2; the mass ratio of glass slag to medium balls is 1-2.5:0.8-1, and the ball milling time is 1.5-6 h; the above ball milling process parameters are used for two ball millings to obtain glass powder with a suitable particle size.
8. The method for preparing glass paste for platinum thin film thermistor according to claim 5, characterized in that: The glass slurry is coated on the surface of the ceramic substrate and then sintered, and the performance of the sintered glass-ceramic element is tested.
Citation Information
Patent Citations
Preparation method of glass ceramic sealing material for platinum resistor film temperature sensing
CN116354604A